2020
DOI: 10.7554/elife.58242
|View full text |Cite
|
Sign up to set email alerts
|

Molecular rationale for antibody-mediated targeting of the hantavirus fusion glycoprotein

Abstract: The intricate lattice of Gn and Gc glycoprotein spike complexes on the hantavirus envelope facilitates host-cell entry and is the primary target of the neutralizing antibody-mediated immune response. Through study of a neutralizing monoclonal antibody termed mAb P-4G2, which neutralizes the zoonotic pathogen Puumala virus (PUUV), we provide a molecular-level basis for antibody-mediated targeting of the hantaviral glycoprotein lattice. Crystallographic analysis demonstrates that P-4G2 binds to a multi-domain si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 89 publications
3
31
0
Order By: Relevance
“…Antigenic site A1 may be similar to the conserved site targeted by mAb 4G2. Many of the mAbs in this group demonstrated broad but incomplete neutralization of authentic virus; this finding is consistent with the occluded nature of some epitopes on Gc ( Li et al, 2016 ; Rissanen et al, 2020 ; Serris et al, 2020 ). The potently neutralizing mAbs we isolated from ANDV-immune donors predominantly targeted Gn.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Antigenic site A1 may be similar to the conserved site targeted by mAb 4G2. Many of the mAbs in this group demonstrated broad but incomplete neutralization of authentic virus; this finding is consistent with the occluded nature of some epitopes on Gc ( Li et al, 2016 ; Rissanen et al, 2020 ; Serris et al, 2020 ). The potently neutralizing mAbs we isolated from ANDV-immune donors predominantly targeted Gn.…”
Section: Discussionsupporting
confidence: 77%
“…Based on competition-binding analysis, at least one antigenic site on Gc is targeted by most cross-neutralizing antibodies (designated here as antigenic site A1). A recently described co-crystal structure of the PUUV mAb 4G2 in complex with Gc shows that this cross-neutralizing mAb binds to a prefusion, monomeric form of Gc ( Rissanen et al, 2020 ). Antigenic site A1 may be similar to the conserved site targeted by mAb 4G2.…”
Section: Discussionmentioning
confidence: 99%
“…nAbs arising following hantavirus infection in humans and from vaccination of animals target both Gn and Gc ( 16 , 25 27 ). Epitope mapping studies based on neutralization escape mutants and peptide mapping have putatively identified a number of neutralizing epitopes on the hantaviral Gn and Gc ( 25 , 27 32 ), and the structure of a neutralizing monoclonal antibody (mAb) in complex with a hantaviral Gc has provided insights into the molecular basis for antibody-mediated targeting of the hantaviral Gc ( 33 ).…”
Section: Introductionmentioning
confidence: 99%
“…Top panel : crystal structure of the ANDV New World orthohantavirus Gc protein ectodomain in its pre-fusion conformation (PDB: 6Y5F [ 154 ]). Second panel : crystal structure of the Old World orthohantavirus PUUV Gc protein ectodomain in its pre-fusion conformation (PDB: 7B09 [ 168 ]). Third panel : crystal structure of the RVFV phlebovirus Gc protein ectodomain in its pre-fusion conformation (PDB: 4HJ1 [ 160 ]).…”
Section: Structure Of Bunyavirus Envelope Glycoproteinsmentioning
confidence: 99%
“…Additionally, the complex of the Gn-Gc heterodimer also revealed a limited structural role of the Gc N-terminal tail in stabilizing the interactions between Gc domains I and III, in the pre-fusion state [ 154 ]. The positioning of the Gc and the nature of Gc-mediated cross-linking of adjacent (Gn-Gc) 4 spikes was also further verified by integrated X-ray and cryoET analysis of HTNV VLPs in complex with the Fab fragment from a bank vole-derived neutralizing monoclonal antibody (mAb) specific to the Gc glycoprotein [ 168 ]. Future work will likely be focused on elucidating the molecular basis for the interaction of the hantaviral (Gn-Gc) 4 spike complex with host cell surface receptors ( Table 1 ) and how this interaction facilitates uptake of the virus into a host cell.…”
Section: Structure Of Bunyavirus Envelope Glycoproteinsmentioning
confidence: 99%